Effect of Glimepiride on Insulin-Stimulated Glycogen Synthesis in Cultured Human Skeletal Muscle Cells - Haupt, Axel; Kausch, Christiana; Dahl, Dominik; Bachmann, Oliver; Stumvoll, Michael; Häring, Hans-U.; Matthaei, Stephan (Diabetes care, 2002)
Effect of Glimepiride on Insulin-Stimulated Glycogen Synthesis in Cultured Human Skeletal Muscle Cells A comparison to glibenclamide Axel Haupt , MD , Christiana Kausch , PHD , Dominik Dahl , MD , Oliver Bachmann , MD , Michael Stumvoll , MD , Hans-U. Häring , MD and Stephan Matthaei , MD From the University of Tübingen, Department of Endocrinology and Metabolism, Tübingen, Germany Abstract OBJECTIVE —To examine the effect of glimepiride on insulin-stimulated glycogen synthesis in cultured human skeletal muscle cells in comparison with glibenclamide. RESEARCH DESIGN AND METHODS —Myotubes derived from glucose-tolerant subjects were incubated with glimepiride or glibenclamide (0–100 μmol/l) for 4 h and with or without insulin (100 nmol/l) for 2 h, and subsequently glycogen synthesis was determined. RESULTS —Glimepiride had no significant effect on basal glycogen synthesis; in contrast, glimepiride caused a dose-dependent increase of insulin-stimulated glycogen synthesis, with a maximal effect of 39.97 ± 8.4% (mean ± SEM, n = 4, P < 0,02). The time course of this glimepiride effect on insulin-stimulated glycogen synthesis showed a peak after 12 h incubation with a half maximal effect after 4 h. Preincubation of the myotubes with wortmannin (100 nmol/l), an inhibitor of phosphatidylinositol (PI)- 3 kinase, caused an inhibition of this glimepiride effect on insulin-stimulated glycogen synthesis. In contrast to glimepiride, incubation of myotubes with glibenclamide (0–100nmol/l), a second generation sulfonylurea, had no significant effect on basal or insulin-stimulated glycogen synthesis. CONCLUSIONS —Incubation of cultured human skeletal muscle cells derived from glucose-tolerant subjects with glimepiride caused a dose-dependent increase of insulin-stimulated glycogen synthesis using therapeutic glimepiride concentrations. This glimepiride effect seems to be mediated via the PI3 kinase pathway. In contrast to glimepiride, glibenclamide had no significant effect on basal or insulin-stimulated glycogen synthesis. These results suggest that glimepiride, beside its well-known effect to stimulate insulin secretion, possess an insulin-sensitizing action in cultured human skeletal muscle cells in support of the concept of an extrapancreatic action of glimepiride. AAS, amphotericin B, penicillin, and streptomycin FBS, fetal bovine serum IRS, insulin receptor substrate PI, phosphatidylinositol SUR, insulin receptor substrate Footnotes Address correspondence and reprint requests to Stephan Matthaei, Department of Medicine IV, University of Tübingen, Otfried-Müller-Str. 10, 72076 Tübingen, Germany. E-mail: stephan.matthaeiatmed.uni-tuebingen.de . Received for publication 17 April 2002 and accepted in revised form 16 September 2002. S.M. and A.H. have received honoraria from Aventis for speaking engagements; Aventis has provided funds for this study; and H.-U.H. received honoraria and grant support from and is on the advisory board of Aventis. A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances. DIABETES CARE